2018
DOI: 10.3390/su10114298
|View full text |Cite
|
Sign up to set email alerts
|

Do International Capabilities and Resources Configure Firm’s Sustainable Competitive Performance? Research within Pakistani SMEs

Abstract: Market conditions in emerging economies are often reported as less stable and volatile. The business sector, especially Small and Medium Enterprises (SMEs) in emerging economies, face several shortcomings including lack of resources, lack of finance, lack of support and lack of human skills, etc. Hence, they look to international support and resources to survive in a long run in the dynamic markets. This research examines the role of international finance, international technology, international experience and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 69 publications
1
46
1
Order By: Relevance
“…When objective data is not available researchers are encouraged to base their research on self-reported data, so we indexed SMEs' performance according to the CFO's assessment of the business's performance using the measurement scale developed by Mikalef and Pateli [100]. This scale was later adapted by Degong et al [12] and Ying et al [15]. CFOs were asked to compare their firm's performance with that of its competitors in eight domains.…”
Section: Measurement Of Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…When objective data is not available researchers are encouraged to base their research on self-reported data, so we indexed SMEs' performance according to the CFO's assessment of the business's performance using the measurement scale developed by Mikalef and Pateli [100]. This scale was later adapted by Degong et al [12] and Ying et al [15]. CFOs were asked to compare their firm's performance with that of its competitors in eight domains.…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…Despite the importance of knowledge resources to the sustainability of SMEs most previous research has focused on other factors, such as competitive advantage, supply chain management and internationalization [12][13][14]. However, Ying et al [15] examined the contribution of managers' intangible capabilities to SMEs' sustainability and concluded that they play an important role in enabling managers to deal with turbulent market conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable competitive performance: We used eight items to measure SCP that were adopted from Degong et al [3]. Owners and managers were asked how their firms have performed on return on equity, return on investment, return on assets, etc.…”
Section: Variables and Measuresmentioning
confidence: 99%
“…Resource base view (RBV) theory depicts that unique, rare, and immutable resources enable firms to gain sustainable competitive advantage [2]. A plethora of research has confirmed the significant influence of resources on firms' performance (e.g., [3][4][5]). However, acquiring resources such as land, equipment, machineries, information, finance, technology, and customers is a great challenge for business organizations.…”
Section: Introductionmentioning
confidence: 99%
“…This study tests the model on the empirical evidence gathered from Asian economies. The reasons for choosing Asian economies are that most of the countries in Asia are placed in low-income countries who are unable to respond to ED unless they receive adequate support in the form of FDI [40]. Asian countries have not yet initiated effective programs and policies to attenuate the adverse in uence of ED [41].…”
Section: Introductionmentioning
confidence: 99%